The implementation of COVID-19 health protocol: a higher students’ perspective - Siti Nurbayani; Moh Dede; Nindita Fajria Utami; Millary Agung Widiawaty (Penerbit Universiti Kebangsaan Malaysia, 2023)
Over two million Indonesians have been exposed to COVID-19. Every day, thousands of new confirmed cases continue to infect people and form local transmission, even though the guidelines for implementing health protocols in efforts against this pandemic have been rolled out. This study aims to reveal how COVID-19 health protocols are being implemented in Indonesia. We collected information from 289 students to observe the surrounding environment by distributing online questionnaires that include parameters for wearing masks and physical distancing. This study used a mix-method approach, in which the statistical and descriptive analysis were carried out sequentially. This study showed that the presence of positive cases does not affect the implementation of health protocols. Mann-Whitney's test also confirmed that there were no significant differences between the COVID-19 transmitted area and the green zone. This condition was caused by a lack of socialization, social exemplarity, mutual reprimand, and enforcement of the rules. The experience of people telling others to wear a mask has a low, significant, and positive correlation with the intensity of reprimanding others. This phenomenon shows that social awareness of implementing health protocols can continue to increase if they are accustomed to self-awareness. The implementation of the health protocol requires assessment to avoid inconsistencies that reduce the compliance of people.